Commercial Land Use and Interjurisdictional Competition - Thiess Büttner (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Commercial Land Use and Interjurisdictional Competition
Keywords: Z00; Z10; Z11; 330